Green Synthesis of Zinc Oxide Particles using Banana Peels and Tea Leaves Extracts for Rhodamine B Photodegradation - Pratomo, Uji; Fransisca, Natasha; Afriani, Zahra; Sinambela, Ayu Jelita; Zahra, Nazwa Alya; Suwarno, Nelson Indarto; Sumeru, Husain Akbar; Kurnia, Irwan; Primadona, Indah; Edwin, Rudiawan (Syarif Hidayatullah State Islamic University, 2024)
Rhodamine B is a widely used dye in the textile sector. However, the wastewater produced during the dyeing process presents a notable source of pollution, contaminating water and posing a threat to aquatic ecosystems due to its presence in liquid waste. Photocatalysis is a technique for breaking down toxic textile dye waste a semiconductor as a catalyst, valued for its high sensitivity and eco-friendly nature. In this research, zinc oxide particles were synthesized via a green synthesis approach using precipitation, employing natural capping agents from banana peel and tea leaf to degrade the synthetic dye of rhodamine B. The catalyst material was characterized using X-ray diffraction (XRD), scanning electron microscope (SEM), and ultraviolet-visible diffuse reflectance (UV-DRS). The photodegradation performance of rhodamine B was determined under UV light exposure for 3 hours. The XRD spectra of ZnO show the specific peaks of 2θ at 31.8°, 34.5°, and 36.3° with a crystallinity value of around 79.50%. The SEM result shows that the morphology of ZnO is in cotton-like form with a minimum band gap of 3.17 eV. The cotton-like ZnO particles demonstrated superior photodegradation efficiency for Rhodamine B, achieving 61.8%, compared to 47.9% with pure ZnO. It suggests that synthesizing ZnO particles with banana peels and tea leaf extracts boosts photodegradation efficiency by up to 20% compared to pure ZnO. This research highlights the potential of utilizing eco-friendly and sustainable methods as a greener approach for reducing waste in environmental applications.